Influence of the rennet type on the quality of Pag Island cheese (Croatian: Paški sir) - Fabijan Oštarić; Neven Antunac; Zvonimir Prpić; Nataša Mikulec (Mljekarstvo)
The aim of this research was to determine the influence of the type of clotting agent on the physical and chemical parameters, as well as on the sensory quality of the Pag Island cheese, which was manufactured with the home-made (traditional) and the commercial rennet. Pag Island cheeses were produced with the home-made rennet obtained by extracting the enzyme from lamb rennet (abomasum), and with the commercially available powdered rennet obtained from the Italian manufacturer “Gruppo Clerici-Sacco”. The production included 7 batches of cheese, with two cheeses in each batch. During 120 days of ripening, the cheeses were periodically sampled after 0, 45, 90 and 120 days, in order to determine the content of dry matter, milk fat, proteins, salt concentration and the pH value of cheese. Also, the content of the total free amino acids from water extracts was determined and the analysis of proteins and polypeptides was conducted by urea polyacrylamide gel electrophoresis (UREA-PAGE). The research did not show a significant (P>0.05) influence of the type of tested rennet on the observed parameters of cheese quality and on its yield. However, this research determined practical significance of the home-made rennet on the higher yield and shorter ripening time in the production of Pag Island cheese.